2013
DOI: 10.1159/000356635
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models for Pendrin-Associated Loss of Cochlear and Vestibular Function

Abstract: The human gene SLC26A4 and the mouse ortholog Slc26a4 code for the protein pendrin, which is an anion exchanger expressed in apical membranes of selected epithelia. In the inner ear, pendrin is expressed in the cochlea, the vestibular labyrinth and the endolymphatic sac. Loss-of-function and hypo-functional mutations cause an enlargement of the vestibular aqueduct (EVA) and sensorineural hearing loss. The relatively high prevalence of SLC26A4 mutations provides a strong imperative to develop rational intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 52 publications
(86 reference statements)
0
21
0
1
Order By: Relevance
“…Studies on mouse models lacking pen drin expression selectively in the endo lymphatic sac (41), or in the cochlea and the vestibular labyrinth (42), showed that pendrin activity is only required during a critical time period of embryonic devel opment and suggested that a temporally and spatially limited therapy directed to the endolymphatic sac and focused on the prenatal phase could restore normal hearing in patients with deafness linked to pendrin mutations (43). On the basis of these considerations and on the find ings presented here, we suggest that pre vention of reduction of expression levels, together with the assistance of proper protein folding, should be regarded as an essential component of potential ther apeutic approaches aimed at restoring or increasing the transport activity of dysfunctional pendrin variants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mouse models lacking pen drin expression selectively in the endo lymphatic sac (41), or in the cochlea and the vestibular labyrinth (42), showed that pendrin activity is only required during a critical time period of embryonic devel opment and suggested that a temporally and spatially limited therapy directed to the endolymphatic sac and focused on the prenatal phase could restore normal hearing in patients with deafness linked to pendrin mutations (43). On the basis of these considerations and on the find ings presented here, we suggest that pre vention of reduction of expression levels, together with the assistance of proper protein folding, should be regarded as an essential component of potential ther apeutic approaches aimed at restoring or increasing the transport activity of dysfunctional pendrin variants.…”
Section: Discussionmentioning
confidence: 99%
“…A Pendred gene, SLC26A4 on chromosome 7q31, was identified coding for the protein pendrin, a transmembrane multifunctional anion transporter highly expressed in the thyroid and inner ear . Murine studies found pendrin to be responsible for the maintenance of the endocochlear potential and fluid homeostasis in the cochlea; therefore, during development the lack of pendrin causes endolymphatic hydrops with gross enlargement of the vestibular aqueduct and endolymphatic sac, lack of proper cochlear turns, and lack of interscalar partitions at the cochlear apex, as also seen in human temporal bones with PS …”
Section: Introductionmentioning
confidence: 99%
“…An increase in endolymph calcium also results from acidification and thus results in toxicity to the stria vascularis and the organ of Corti. 15 Potential limitations of the study include bias in the interpretation of the healthy cohort because the experienced reader did have a preconceived theory of the appearance of the normal R2 notch. Also, while the inexperienced readers had minimal prior exposure to interpreting MR imaging of the temporal bone, other findings encountered in IP-II malformation may have been seen and affected their interpretation.…”
Section: Rocmentioning
confidence: 99%
“…The SLC26A4 gene codes for the protein pendrin, which is a chloride/bicarbonate anion exchanger that serves to increase the pH in the endolymph compartment by secreting bicarbonate. 15 Pendrin protein expression in the endolymphatic sac is critical in the development of the mammalian inner ear as demonstrated in a murine model. The absence or reduction in pendrin expression results in acidification and abnormal expansion of the developing inner ear.…”
Section: Rocmentioning
confidence: 99%